2001
DOI: 10.1093/humrep/16.8.1682
|View full text |Cite
|
Sign up to set email alerts
|

Perifollicular vascularity as a potential variable affecting outcome in stimulated intrauterine insemination treatment cycles: a study using transvaginal power Doppler

Abstract: These data would suggest that perifollicular vascularity has an important role to play in the outcome of IUI cycles, and that power Doppler has the potential to refine the management of assisted reproduction treatment cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
6
40
1
Order By: Relevance
“…Previous studies also assessed these parameters in cattle (Siddiqui et al 2008. ), horses (Silva et al 2006), and humans (Coulam et al 1999, Bhal et al 2001, Borini et al 2001, and encountered a positive correlation between FL vascularity and fertility. In the present study, CL vascularity was positive related with pregnancy rate at the time of embryo transfer, but no relationship with fertility was noted when follicle size and vascularity were measured at the time of AI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also assessed these parameters in cattle (Siddiqui et al 2008. ), horses (Silva et al 2006), and humans (Coulam et al 1999, Bhal et al 2001, Borini et al 2001, and encountered a positive correlation between FL vascularity and fertility. In the present study, CL vascularity was positive related with pregnancy rate at the time of embryo transfer, but no relationship with fertility was noted when follicle size and vascularity were measured at the time of AI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since it is a non invasive technique and with reliable application, it is a useful tool to target new reproductive diagnoses. The evaluation of perifollicular vascularity was done in cows (Siddiqui et al 2008), women (Coulam et al 1999, Bhal et al 2001, Borini et al 2001, and mares (Silva et al 2006), and in all of these species was detected greater vascularity in the preovulatory follicle wall in individuals that became pregnant after mating.…”
Section: Introductionmentioning
confidence: 99%
“…In women, several studies have indicated that the blood flow in the wall of the preovulatory follicle is an indication of the potential success of assisted reproductive techniques. Preovulatory examination of colour Doppler signals of blood flow in the follicular wall (Bhal et al 2001) and vascular resistance distal to an intraovarian artery by spectral Doppler indices (Du et al 2006) are useful for assessing the quality of the oocyte. Bhal et al (2001) reported that follicle vascularity is a factor in determining the success of pregnancy establishment after intrauterine insemination.…”
Section: Introductionmentioning
confidence: 99%
“…Preovulatory examination of colour Doppler signals of blood flow in the follicular wall (Bhal et al 2001) and vascular resistance distal to an intraovarian artery by spectral Doppler indices (Du et al 2006) are useful for assessing the quality of the oocyte. Bhal et al (2001) reported that follicle vascularity is a factor in determining the success of pregnancy establishment after intrauterine insemination. Greater blood flow in the wall of the preovulatory follicle also has been associated with improved rates of in vitro fertilisation (IVF) and embryo development (Bhal et al 1999, Coulam et al 1999, Huey et al 1999, Du et al 2006, Shrestha et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation